Dental remains of immature individuals of Rhynchotherium blicki (Frick 1933) of San Gerardo de Limoncito, Coto Brus, Costa Rica - Valerio, Ana L. (2011)
Remains of juvenile individuals of Rhynchotherium blicki (Frick 1933) mastodon have been collected from sediments of the Upper Miocene (Late Hemphillian) locality of San Gerardo de Limoncito, corresponding with the top of Curré Formation. The recovered material, includes two second left upper deciduous molars and three frag- ments of tusks that were associated to the false gavial Gavialosuchus americanus (Sellards, 1915), remains of a soft shelled turtle Apalone sp., teeth of selachians (sharks and rays) and other icthyolites. The ecological requirements of the taxa suggest the existence of different environmental conditions from open grassland habitats to more closed marine environments like estuaries.